2017
DOI: 10.18632/oncotarget.16572
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent effects of cadmium on tumor angiogenesis

Abstract: Angiogenesis is crucial for tumor growth and metastasis. Cadmium (Cd) exposure is associated with elevated cancer risk and mortality. Such association is, at least in part, attributable to Cd-induced tumor angiogenesis. Nevertheless, the reported effects of Cd on tumor angiogenesis appear to be either stimulatory or inhibitory, depending on the concentrations. Ultra-low concentrations of Cd (<0.5 μM) inhibit endothelial nitric oxide synthase activation, leading to reduced endothelial nitric oxide production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 136 publications
(385 reference statements)
2
31
0
Order By: Relevance
“…With respect to plausible biological mechanisms that could explain the observed inverse associations, it has been reported that the effects of cadmium on tumor angiogenesis in breast cancer cells and other tumor models, can be either stimulatory or inhibitory, depending on the concentrations. 42,43 Ultra-low concentrations of cadmium (<0.5 μM) inhibit endothelial nitric oxide synthase (eNOS) activation, leading to reduced eNOS production and attenuated tumor angiogenesis. 44 Additionally, cadmium in high concentrations (>10 μM) induces both endothelial cells apoptosis via the activation of caspase-3, resulting in destruction of tumor vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to plausible biological mechanisms that could explain the observed inverse associations, it has been reported that the effects of cadmium on tumor angiogenesis in breast cancer cells and other tumor models, can be either stimulatory or inhibitory, depending on the concentrations. 42,43 Ultra-low concentrations of cadmium (<0.5 μM) inhibit endothelial nitric oxide synthase (eNOS) activation, leading to reduced eNOS production and attenuated tumor angiogenesis. 44 Additionally, cadmium in high concentrations (>10 μM) induces both endothelial cells apoptosis via the activation of caspase-3, resulting in destruction of tumor vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is the first, to our knowledge, to provide evidence for the effect of Cd on CFH expression and production in glomeruli, suggesting Cd as a crucial regulator of the innate immune system. Cd affects multiple organs, including liver and kidney, and the vascular system is also one of the primary targets of Cd-induced toxicity (42,43). At lower concentrations, Cd does not induce cytotoxicity in endothelial cells (7,9,44) but increases expression of vascular hemostastic factors, such as tissue factor and von Willebrand factor (45).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of angiogenesis has thus been regarded as a valuable new approach to cancer therapy (14). A number of stimulators and inhibitors regulate angiogenesis (15). In the case of PKD1, a consensus exists with regard to its proangiogenic and thus proproliferative role whatever the cell model [endothelial progenitor cells (EPC) or cell lines] or the species (human or even zebrafish).…”
Section: Pkd1 Stimulates Angiogenesis a Key Determinant In Cancer Dementioning
confidence: 99%